Unraveling Complexity: The Role of Hardware and Software in Building a Resilient Management Information System at SMKN 1 Bengkalis - Nopita; Nur Atika; Siti Hardianti; Titin Sumarni (Interkoneksi: Journal of Computer Science and Digital Business, 2024)
The development of management information systems has changed the way decisions are made at various managerial levels. Information technology, especially the internet, allows easy access to relevant data and powerful analytical tools, enabling managers to make better and faster decisions, increasing efficiency and productivity in organizational operations. The computer as the main tool in the information system has two main components, namely hardware and software. Computer hardware, such as the mouse, keyboard, and CPU, are the physical parts that enable data processing, while the software provides the processes to complete these tasks. The operating system, as the main software on a computer, connects hardware and other software, ensuring that various applications can run smoothly and use computer resources efficiently. In building a robust management information system, proper integration between hardware and software is essential. The synergy between the two ensures that the resulting product can run well and meet user needs and project specifications. Some management information system applications that utilize both hardware and software include ERP, SCM, TPS, OAS, KWS, IMS, DSS, ES, GDSS, CSCWS, and ESS. By understanding the role and relationship between hardware and software in management information systems, organizations can build a resilient IT infrastructure that supports their operational success.